2009
DOI: 10.1590/s0102-311x2009001500006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of methodology on the results of economic evaluations of varicella vaccination programs: is it important for decision-making?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For instance, in a study on economic evaluation of varicella vaccination, the vaccine was not acceptable for a base-case analysis (not including the indirect cost). However, when the indirect cost was included, the vaccine is acceptable [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study on economic evaluation of varicella vaccination, the vaccine was not acceptable for a base-case analysis (not including the indirect cost). However, when the indirect cost was included, the vaccine is acceptable [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness of varicella vaccination has been analyzed in several studies. [14][15][16][17][18] The results suggest that dynamic transmission models are more accurate than static models at capturing the indirect effects of varicella vaccination (e.g., herd immunity, age distribution of varicella cases, incidence of herpes zoster), 14,16,17 and, thus, dynamic transmission models have become the gold standard. However, publications on budget-impact models in low-and middleincome countries are sparse, despite their importance for decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Zhou and colleagues have shown that the two-dose regimen is cost-effective when compared with no vaccination but not when compared with the one-dose regimen [Zhou et al 2008]. Moreover, it is important to understand that there is a considerable heterogeneity in the methodologies used in different studies which have an impact on their results [Soarez et al 2009]. More specifically, the type of model used (static versus dynamic), the perspective examined (whether society's perspective is added to that of providers), the inclusion of the herd immunity effect and vaccination coverage and the different amounts used for vaccine price and parental wages also had a significant impact on the computed results.…”
Section: Cost-effectiveness Studies Evaluating the Introduction Of Vamentioning
confidence: 99%